Mencipta Puisi Berbasis Pemahaman Unsur-unsur Pembangun Puisi Siswa SMA Assa’adah, Gresik - Rohmah, Nur; Pramulia, Pana; Pramujiono, Agung (Institut Riset dan Publikasi Indonesia (IRPI), 2024)
This service aims to improve the literacy and creativity skills of Assa'adah Gresik High School students through training in creating poetry which focuses on the building blocks of poetry, such as theme, diction, imagery, figures of speech, rhyme and rhythm. With interactive and project-based learning methods, students are given the opportunity to understand, apply and develop original poetry writing skills. The results of the activity showed a significant increase in students' understanding and ability to write poetry, which was documented in a poetry anthology. This program also encourages students' appreciation of literature, increases their confidence in expression, and contributes to the development of literary literacy in the school environment.